Viscoelastic Wave Equation with Logarithmic Nonlinearities in ℝn (Journal of Partial Differential Equations, 2018)
In any spaces dimension, we use weighted spaces to establish a general decay rate of solution of viscoelastic wave equation with logarithmic nonlinearities. Furthermore, we establish, under convenient hypotheses on g and the initial data, the existence of weak solution associated to the equation.